A Review of Pathogenesis of Hypertension: Ayurvedic approach - Gangwar, Sudeep Singh; Kumar, Avadhesh; Singh, S K (International Research Journal of Ayurveda & Yoga, 2021)
Hypertension has become a global burden, except for genetic multifactorial influences, it is due to faulty & stressful life style. Till now the actual etiopathology of hypertension is unknown, due to lack of knowledge of actual etiopathogenesis, we are unable to do complete cure of hypertension and that’s why the mortality and morbidity shows a considerable %. It is the most important and single factor of cardiovascular disorder, coronary disorder, CHF and CRF. In Ayurveda there is no straight literature present about HTN or Uchha raktachapa but on the basis of symptoms it can be correlate with the Vata vyadhi named raktgata vata (hypertension) which is explained in Ayurveda. In this article we try to explain its etiopathogenesis (Samprapti) in ayurvedic terms which is made on the basis of involved dosha, dhatu (body tissues), Srotasa (channels) and other factors. It can be considered as Vata dominant Tridoshaja vyadhi (Disease caused by Tridosha) & Ama (collection of toxins) is involved in its pathogenesis. So, it can be effectively treated by Tridosha pacifying, Agnivardhaka chikitsa (enhancing digestive strength).